Une affaire de femmes : la chanson comique en France - Isbelle Marc (Çédille: Revista de Estudios Franceses, 2013)
French female artists over the last century, including Yvette Guibert, Brigitte Fontaine, Colette Renard and Clarika, among many others, have successfully used different forms of humour in their songs. This article aims to study how feminine humour is created in the French chanson and how it evolves throughout time. Considering humour both as a means and as a consequence of feminine agency, it will explore symbolic and aesthetic issues related to humoristic chanson as regard to the creation of feminine identity in the French context. For that purpose, it will first address the specificities of the relation between women and music and between women and humour. Then, it will analyse several representative songs in this respect, such as Fais-moi mal, Johnny by Magali Noël, Déshabillez-moi by Juliette Gréco and Les crêpes aux champignons by Olivia Ruiz, among others. Drawing from these examples, humour will be regarded both as a means and as a consequence of feminine agency.